Virtual Vanguard: Virtual Vanguard: Content Creators as Pillars of Modern Digital Marketing - Palomino-Flores, Paola (2024)
The study investigates how it analyzes the effect of marketing strategies on content creators’ broadcasts and their influence on brand recognition. In the study conducted with 300 consumers, it was revealed that strategies integrating creativity and emotion into the content are much more effective than direct promotions. Content creators who organically and creatively incorporate brands into their content foster greater interest and preference for these brands among their audience. These findings suggest a shift towards digital marketing strategies focused on the creative and natural integration of brands into content, which is crucial for improving their perception. This approach, which prioritizes harmonious narrative between brands and content creators, marks a future for digital marketing that transcends the transactional, seeking to emotionally connect with audiences and generate genuine dialogue in the dynamic environment of live streaming.